2017
DOI: 10.23889/ijpds.v2i1.406
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic linkage of national immunisation and state-based health records for a cohort of 1.9 million births to evaluate Australia’s childhood immunisation program

Abstract: IntroductionSeveral countries have developed national immunisation registers, but only the Nordic countries have linked their registers to other health data in order to comprehensively evaluate the 'real world' effectiveness of vaccines. Nordic countries can link datasets deterministically using the national person identifier, but most countries, including Australia, don't have such an identifier to enable this type of linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…The full details of assembling the linked dataset through probabilistic linkage across three linkage centres are provided elsewhere. [8,9] In brief, the cohort comprised 1,953,881 infants that had both a registered birth record and a perinatal data record. Aboriginal status was derived using a multi-stage median algorithm, described previously [10] using information from all linked datasets in the study, excluding deaths, and based on Australia's national best practice guidelines for data linkage activities relating to Aboriginal and Torres Strait Islander people.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The full details of assembling the linked dataset through probabilistic linkage across three linkage centres are provided elsewhere. [8,9] In brief, the cohort comprised 1,953,881 infants that had both a registered birth record and a perinatal data record. Aboriginal status was derived using a multi-stage median algorithm, described previously [10] using information from all linked datasets in the study, excluding deaths, and based on Australia's national best practice guidelines for data linkage activities relating to Aboriginal and Torres Strait Islander people.…”
Section: Study Populationmentioning
confidence: 99%
“…DTP immunisation records for the study cohort between 1996 and 2013 were extracted from AIR and probabilistically linked at the Australian Institute of Health and Welfare as described previously. [8,9] In brief, immunisation data from AIR were linked to the birth register based on a matched linkage rate of 99.3% (similar to a sensitivity measure) with a corresponding linkage accuracy of 99.0% (similar to a positive predictive value measure). Duplicate immunisation records with the same immunisation date and vaccine dose number were removed.…”
Section: Vaccination Recordsmentioning
confidence: 99%
“…Despite this, gaps in surveillance data remain, 2,3,7 impacting on the system’s utility to support the development of evidence‐based prevention and control efforts. Data linkage is recognised as a valuable method to close surveillance gaps and enhance the value of publicly held health data 10,24,48,61,62 . To our knowledge, this is the first time that jurisdictional practices relating to the use of data linkage in the communicable disease setting in Australia have been described.…”
Section: Resultsmentioning
confidence: 95%
“…In our study, none of the jurisdictions reported using data linkage methodologies to improve vaccination status in local notifiable disease registries. We contend, that while the use of data linkage may not be practicable during an immediate public health response, gaps in surveillance data relating to vaccination status could be addressed retrospectively to improve completeness of this key variable in local and national surveillance systems, thereby also improving cross‐jurisdictional evaluation of national immunisation programs 24 . Using the AIR in this manner would accord with the stated purposes of the register as set out in the Australian Immunisation Register Act 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation